A comparison of outcomes according to different diagnostic systems for delirium (DSM-5, DSM-IV, CAM, and DRS-R98). (14th September 2017) - Adamis, Dimitrios; Meagher, David; Rooney, Siobhan; Mulligan, Owen; McCarthy, Geraldine
ABSTRACT: Studies indicate that DSM-5 criteria for delirium are relatively restrictive, and identify different cases of delirium compared with previous systems. We evaluate four outcomes of delirium (mortality, length of hospital stay, institutionalization, and cognitive improvement) in relation to delirium defined by different DSM classification systems. Prospective, longitudinal study of patients aged 70+ admitted to medical wards of a general hospital. Participants were assessed up to a maximum of four times during two weeks, using DSM-5 and DSM-IV criteria, DRS-R98 and CAM scales as proxies for DSM III-R and DSM III. Of the 200 assessed patients (mean age 81.1, SD = 6.5; and 50% female) during hospitalization, delirium was identified in 41 (20.5%) using DSM-5, 45 (22.5%) according to DSM-IV, 46 (23%) with CAM positive, and 37 (18.5%) with DRS-R98 severity score >15. Mortality was significantly associated with delirium according to any classification system, but those identified with DSM-5 were at greater risk. Length of stay was significantly longer for those with DSM-IV delirium. Discharge to a care home was associated only with DRS-R98 defined delirium. Cognitive improvement was only associated with CAM and DSM-IV. Different classification systems for delirium identify populations with different outcomes.